Inovasi Teknologi Beton Ringan dengan Penggunaan Foam Agent ADT Pengaruh terhadap Sifat Mekanik Beton dan Komposisi Optimal - Dani Pasaribu; Muhammad Ahdi Hafizha (LPPM Universitas Abdurrab, 2025)
As a region prone to earthquakes, lightweight concrete is strongly recommended to be used in construction development in Indonesia, especially buildings. If lightweight concrete is used as a non-structural element, it will reduce the total mass of the building which causes the load to be smaller and the design to be more economical as well. The addition of foam agent ADT in the concrete mix will produce air bubbles that can reduce the specific gravity of the concrete but will also reduce the compressive strength of the concrete. The addition of additive foam concrete ADT to the concrete mixture which has a function other than as a plasticizer also serves to stabilize the air bubbles produced by the foaming agent. The purpose of this research is to get the best composition of ADT foaming agent in concrete mixtures with additional additive foam concrete so as to produce better concrete resistance performance, determine the compressive strength, and water absorption of concrete with the use of variations in the composition of ADT foaming agent and the addition of additive foam concrete. The results show that the greater the density value of foam concrete, the higher the compressive strength value. While the percentage of water absorption produced in this study, the greater the density value of concrete with added foam, the smaller the absorption rate